Dilema Recall Dalam Sistem Ketatanegaraan Indonesia - Nasef, Muhammad Imam (STAIN Jurai Siwo Metro, 2011)
Abstract In Indonesia ârecallâ is meant as a fall down or the dismissal of a member of Parliament (DPR and MPR) through the mechanism of substitution between time (PAW). Various instruments governing law concerning dismissal and shifting between the time of members of Parliament illustrated that political party has such a huge role on it. This paper discusses the recall of members of Parliament in the parliamentary perspective on Indonesia. This paper is based on a review of librarianship data with a descriptive-qualitative method. The approach used is a juridical approach. Based on the review in this paper, it can be concluded that the role of politics is more dominant than the laws and regulations in the determination of recall for members of Parliament. The leadership of a political party is the only party which can propose the dismissal. Therefore, it is reasonable when the recall among senayan politicians is regarded as a ghost or even defective democracy.Keywords : Recall, Popular Sovereignty, Political Parties, Parliamentary Law